Enhancing Students’ Speaking Skills in Speaking for Academic Purposes Subject through Active Debate At The 4th Semester in Academic Year 2023/2024 Universitas Panca Sakti Bekasi - Agustin, Iswandini; Rusmiati, Yanti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
In Speaking for Academic Purposes, the students must be able to speak actively. And there are some materials on this subject, one of them is Debate. Active debate is one way to improve students' speaking skills. So, the purpose of this study was to improve students’ speaking skills through Active Debate. This research method is classroom action research, which is used in two cycles, and each cycle has four steps: planning, action, observing, and reflection. The data presented in this study were obtained from observations, interviews, and students’ speaking scores. The subjects of this research were fifteen students in the fourth semester of the Speaking for Academic Purposes Class at Panca Sakti University. In the study, the researcher got the result, namely the percentage of speaking scores. The score for students speaking test in cycle one was 52.36 % passed, and 47.64 % failed; Passed 78,2% and 21.8% failed in cycle two. So, the increase in yield in cycles 1 and 2 is 25.84%. And score for aspects of observation in cycle one is 71,38% passed and failed: 28,62%; passed 92,5% and 7,5% failed in cycle two. Based on the data above, it can be concluded that learning English, especially speaking through active debate, can improve students’ speaking skills.